A proposal for a healthcare environment with a real-time approach. (24th April 2020) - Gomes, Eliza H.A.; Dantas, Mario A.R.; Plentz, Patricia D.M.
The increased use of IoT has contributed to the popularisation of environments that monitor the daily activities and health of the elderly, children or people with disabilities. The requirements of these environments, such as low latency and rapid response, corroborate the usefulness of associating Fog Computing with healthcare environments since one of the advantages of Fog Computing is to provide low latency. Because of this, we propose the use of a hardware and software infrastructure capable of storing, processing and presenting monitoring data in real-time, based on Fog Computing paradigm. Additionally, we propose the structuring of sensors for the implementation of a simulated healthcare environment, as well as the processing logic for the presentation of results referring to the health of the user.